Effect of P21‐activated kinase 1 (PAK‐1) inhibition on cancer cell growth, migration, and invasion. Issue 5 (6th September 2019) - Najahi‐Missaoui, Wided; Quach, Nhat D.; Jenkins, Amber; Dabke, Isha; Somanath, Payaningal R.; Cummings, Brian S.
Abstract: P21‐activated kinase‐1 (PAK‐1) is a serine/threonine kinase involved in multiple signaling pathways that mediate cellular functions such as cytoskeletal motility, cell proliferation, and survival. PAK‐1 expression is altered in various cancers, including prostate and breast. Our recent studies showed that prostate cancer cells expressing higher levels of PAK‐1 were resistant to the cytotoxic effects of the PAK‐1 inhibitor, inhibitor targeting PAK‐1 activation‐3 (IPA‐3), compared to those with lower expression. This study expanded these findings to other cancers (breast and melanoma) by testing the hypothesis that genetic and pharmacological inhibition of PAK‐1 alters cell growth, migration, and invasion in prostate, breast, and skin cancer cell lines. We also tested the specificity of IPA‐3 for PAK‐1 and the hypothesis that gene silencing of PAK‐1 altered the efficacy of sterically stabilized liposomes (SSL) containing IPA‐3 (SSL‐IPA‐3). PAK‐1 expression was identified in four different breast cancer cell lines, and in a melanoma cell line. The expression of PAK‐1 correlated to the IC50 of IPA‐3 as measured by MTT staining. PAK‐1 inhibition using shRNA correlated with decreased cell migration and invasion in prostate cancer DU‐145 and breast cancer MCF‐7 cells. Decreased migration and invasion also correlated to decreased expression of E‐cadherin and alterations in C‐X‐C Chemokine Receptor type 4 and Homing Cell Adhesion Molecule expression. PAK‐1 inhibition increased the cytotoxicity of IPA‐3, and the cytotoxicity of SSL‐IPA‐3 to levels comparable to that of free drug. These data demonstrate that both pharmacological and molecular inhibition of PAK‐1 decreased growth in prostate, breast, and melanoma cancer cell lines, and increased the toxicity of IPA‐3 and its liposomal formulation. These data also show the specificity of IPA‐3 for PAK‐1, are some of the first data suggesting that IPA‐3 is a therapeutic treatment for breast cancer and melanoma, and demonstrate the efficacy of liposome‐encapsulated IPA‐3 in breast cancer cells.